2015
DOI: 10.1111/adb.12244
|View full text |Cite
|
Sign up to set email alerts
|

Which alcohol use disorder criteria contribute to the association ofADH1Bwith alcohol dependence?

Abstract: Although alcohol dependence (AD) is approximately 50% heritable, little is known about how specific genetic loci affect AD risk. In a genome-wide association study (GWAS), we identified highly significant associations between two population-specific functional variants in the alcohol dehydrogenase 1B gene (ADH1B) and AD in African-Americans (AAs; rs2066702) and European-Americans (EAs; rs1229984). In the current study, we determined which specific diagnostic criteria contributed to the observed associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
2
18
0
3
Order By: Relevance
“…Although GWS was only noted in the trans-ancestral (EA + AA) analysis, as shown in Table S7, rs1229984 was associated with the AD criterion count and criteria indexing physiological dependence and Desire to cut drinking at GWS levels, and with other AD criteria at nominal levels of significance. Similar to another study, 16 we found that while rs1229984 was associated with each individual criterion (EA all P < 3.61E−04; EA + AA all P < 4.54E 6 However, for DSM-IV AD criterion count, rs1229984 was GWS in both the EA and EA + AA analyses.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although GWS was only noted in the trans-ancestral (EA + AA) analysis, as shown in Table S7, rs1229984 was associated with the AD criterion count and criteria indexing physiological dependence and Desire to cut drinking at GWS levels, and with other AD criteria at nominal levels of significance. Similar to another study, 16 we found that while rs1229984 was associated with each individual criterion (EA all P < 3.61E−04; EA + AA all P < 4.54E 6 However, for DSM-IV AD criterion count, rs1229984 was GWS in both the EA and EA + AA analyses.…”
Section: Discussionsupporting
confidence: 87%
“…9 Genomic data also support this variability with Palmer et al reporting a SNP-based heritability ranging from 13% (Time spent drinking) to 34% (Tolerance). 16 Another strategy to improve the ability to detect variants contributing to DSM-IV AD is to consider the severity of the AD. In addition, in one study, the observed associations with ADH1B loci were also differentially attributable to Tolerance, Withdrawal, Drinking more than intended, and Time spent drinking, relative to other criteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, the present-day diagnostic framework for mental disorders might, without drastic revision, be improved with the aid of such measures. For addictive disorders, the story is much the same and, for example, ADH1B genotypes (alcohol), while associated with DSM criteria, are not integrated within this framework [11]. Furthermore, downregulation of striatal dopamine D2 receptor protein expression, observable by raclopride PET [12] and disturbances of the stress axis [13,14], have long been recognized to occur among patients who are addicts, but have not been incorporated into clinical practice, or used in clinical research in any systematic way.…”
Section: Intermediate Phenotypes and Endophenotypesmentioning
confidence: 99%
“…We chose these variants on the basis of numerous GWAS (Gelernter et al, 2014;Xu et al, 2015) and candidate-locus studies (Sherva et al, 2010;Hart et al, 2015;Jensen et al, 2015), and a recent meta-analysis of genetic studies of nicotine and alcohol traits (Buhler et al, 2015) and GWAS performed previously in different population groups (David et al, 2012;Gelernter et al, 2014).…”
Section: Genotype Datamentioning
confidence: 99%